Problems of Waqf Mosque Management: A Contemporary Fiqh Perspective with Historical Viewpoints - Dzakirah, Nadiva Fahriyyah Ayu; Khusnuddin (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
Introduction: The existence of problems in managing mosque waqf is a problem in an organization or institution. The renewal of waqf in today's thinking can be a solution to management problems. Methods: This research aims to determine the problems in managing waqaf mosques from a historical perspective. The method used is a descriptive qualitative method. Data collection techniques use interviews and documentation. Results: The results of the research show that the management of waqaf mosques, which previously had problems, is now better managed because there are management ideas that can make the management of the mosque run well. Conclusion and suggestion: The problem of waqf mosques can be resolved by returning to the benefits of mosques, namely that mosques are places of worship for muslims who do not respect any sect.